Utilizing ion-exchange resin to improve recovery from organic shock-loading in an AnMBR treating sewage sludge. (1st December 2017) - Martin-Ryals, Ana D.; Schideman, Lance C.; Guy, Kathryn
Abstract: The addition of ion-exchange resin in a two-phase continuous AnMBR system treating primary sludge at ambient temperature (20 °C) was investigated as a means to improve reactor recovery after organic shock-loading. Four commercially available anion-exchange resins were evaluated for their ability to sorb soluble organics, specifically volatile fatty acids (VFA), from AnMBR effluent. The strong-base resin, Purolite TANEX, was determined the best resin for deployment in the continuous AnMBR having achieved the greatest removal of soluble chemical oxygen demand (sCOD) (up to 36%) and acetic acid (up to 48%) in preliminary batch testing. Addition of 100 and 300 g/L TANEX in the AnMBR system improved effluent quality reducing effluent COD concentrations by 48 and 75%, respectively, under normal operating conditions. After shock-loading with 16, 000 mg COD/L as acetic acid, reactor recovery in terms of methane production was 9–58% faster with the addition of TANEX than without, under controlled pH conditions (pH: 7.4). After shock-loading the system twice without the addition of TANEX it was found that recovery improved by 19% suggesting that acclimation of the microbial community also played a role in reactor recovery. Microbial community analysis using 16 S Illumina MiSeq sequencing confirmed changes in the microbial community did occur in response to shock-loading, with higher relative abundance of Methanoscarcina in the majority of post-shock-load microbial communities. The highest relative abundance of Methanoscarcina (51–58%) was seen during operating periods with the addition of TANEX resin, leading to the conclusion that addition of the TANEX resin benefited reactor recovery by serving as a temporary physio-chemical sink for the excess acetic acid, allowing the microbial community time to adjust to their new environmental conditions and become better able to process the higher levels of acetic acid associated with the organic shock. Graphical abstract: Image 1 Highlights: Strong-base anion exchange (SBA-IX) resin provided better sorption of VFA than GAC. Addition of SBA-IX resin improved AnMBR effluent quality via sorption of sCOD. AnMBR recovery after organic shock-loading was faster with the addition of SBA-IX. SBA-IX resin supported acclimation of microbial community to higher organic load.